The uptake and subcellular distribution of radio-labelled metabolites of digitoxin in the guinea-pig isolated perfused heart. - Dutta, S (1976)
1 Comparisons were made of the uptake and inotropic effects of concentrations of 0.1 muM of digitoxin and its cleavage products digitoxigenin-bis-digitoxoside, digitoxigenin-mono-digitoxoside and digitoxigenin in the isolated perfused hearts of guinea-pigs. 2 Digitoxin produced the greatest inotropic responses in this series, while the sequence of cleavage products produced progressively smaller responses. 3 The uptake of digitoxin was significantly higher than that of the three metabolites, and the uptake of metabolites became progressively less with cleavage. The highest binding in each case was found in the microsomal fraction. 4 The uptake of all four digitaloids was reduced when the potassium in the perfusion medium was increased.